Composite ferrite for self-biased circulator and method for manufacturing the same

CN120682026BActive Publication Date: 2026-10-30HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510834281.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2026-10-30
Estimated Expiration
2045-06-20

AI Technical Summary

Technical Problem

但上述公开方法中高介YIG铁氧体在具备高介电常数的同时居里温度较低,会导致器件的使用温度受到限制

Benefits of technology

[0062]本发明提供的自偏置环行器用复合铁氧体,采用BaM铁氧体与LiZn铁氧体相结合,LiZn铁氧体具有高剩磁比、低线宽和高居里温度的优势,通过高能湿磨、磁场取向成型及热处理,有效调控了晶粒晶界特性,提高了取向度,增加了饱和磁化强度,配合取代元素种类及取代量,改善了复合铁氧体的微观结构与电磁特性,适用于工业规模化生产。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to a composite ferrite for a self-biased circulator and a preparation method thereof. The composite ferrite is prepared by combining BaM ferrite and LiZn ferrite. The LiZn ferrite has the advantages of high residual magnetism ratio, low line width and high Curie temperature. The grain boundary characteristics are effectively controlled, the orientation degree is improved, and the saturation magnetization is increased through high-energy wet grinding, magnetic field orientation forming and heat treatment. In combination with the types and substitution amounts of substitution elements, the microstructure and electromagnetic characteristics of the composite ferrite are improved, and the composite ferrite is suitable for industrial scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ferrite material preparation technology, specifically to a composite ferrite for a self-biased circulator and its preparation method. Background Technology

[0002] A microwave circulator is a non-reciprocal multiport microwave device capable of unidirectional transmission of electromagnetic waves. This characteristic makes it widely used in radar, communication systems, antenna duplexers, and other applications. Traditional microwave circulators require a large built-in permanent magnet to provide a DC bias field. With the trend towards higher frequency bands and miniaturization in microwave technology, the presence of the permanent magnet makes it difficult to achieve overall miniaturization of the transceiver system, thus limiting the integration and portability of microwave systems.

[0003] Self-biased ferrite materials possess a large magnetocrystalline anisotropy field, enabling the formation of a self-biased internal field. This eliminates the need for an external permanent magnet to provide a bias magnetic field for the circulator, allowing the magnetic moment to resonate ferromagnetically with microwaves or millimeter waves even without an external steady magnetic field or with a very small steady magnetic field, thus achieving self-biasing of the circulator. Devices employing self-biased ferrites can significantly reduce size and weight, meeting the demands of modern electronic devices for integration and lightweight design.

[0004] Current research on self-biased ferrites mainly focuses on improving their performance and optimizing fabrication processes to meet the development demands of microwave devices for higher frequencies, miniaturization, and lower losses. CN118955113A discloses a soft-hard magnetic microwave ferrite coupling material and its preparation method. The ferrite coupling material includes YIG and BaM microwave ferrites. BaM ferrite and high-dielectric YIG powder are mixed, ground, and pre-calcined in different proportions to couple the soft magnetic phase (high-dielectric YIG ferrite) and the hard magnetic phase (BaM ferrite), achieving high-micro-value coupling in the hard magnetic phase. r / M s and H c The properties are coupled onto a high-dielectric-low-loss soft magnetic phase. CN119176714A discloses a C-band ultra-low-loss self-biased hexagonal gyromagnetic ferrite material and its preparation method. BaM ferrite and high-dielectric YIG powder are mixed in different proportions, ball-milled, and pre-calcined to grow high-dielectric-low-loss YIG gyromagnetic ferrite material particles with properties that are coupled onto a high-dielectric-low-loss soft magnetic phase. r / M s and H c Characteristic BaM hexagonal gyromagnetic ferrite material, achieving high M in hard magnetic phase r / M s and H cThe properties are combined with a high-dielectric- and low-loss soft magnetic phase. However, the high-dielectric YIG ferrite in the above-disclosed methods has a low Curie temperature while possessing a high dielectric constant, which limits the operating temperature of the device. In addition, some methods contain In2O3 in their formulations, which increases the production cost of the material and limits its practicality. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a composite ferrite for self-biased circulators and its preparation method, which improves the microstructure and electromagnetic properties of the composite ferrite, giving it advantages such as high remanence ratio and low linewidth.

[0006] To achieve this objective, the present invention employs the following technical solution:

[0007] In a first aspect, the present invention provides a composite ferrite for a self-biased circulator, wherein the raw materials for preparing the composite ferrite for the self-biased circulator include LiZn ferrite, BaM ferrite, and dopants.

[0008] The mass ratio of LiZn ferrite to BaM ferrite is 1:(1-2.5), for example, it can be 1:1, 1:1.5, 1:2, 1:2.2 or 1:2.5, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0009] The LiZn ferrite is: Li 0.5-0.5a Zn a Fe 2.4-0.5a-b Co b Mn 0.1 O4, where 0.27≤a≤0.33, 0.02≤b≤0.06.

[0010] The value 0.27≤a≤0.33 can be, for example, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32 or 0.33, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0011] The value 0.02≤b≤0.06 can be, for example, 0.02, 0.03, 0.04, 0.05 or 0.06, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0012] The BaM ferrite is: Ba 1-x-y Ca x La y Fe 12-z Co z O 19 , where 0.18≤x≤0.28, 0.34≤y≤0.44, and 0.2≤z≤0.3.

[0013] The value 0.18≤x≤0.28 can be, for example, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27 or 0.28, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0014] The value 0.34≤y≤0.44 can be, for example, 0.34, 0.35, 0.36, 0.38, 0.4, 0.42, or 0.44, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0015] The value 0.2≤z≤0.3 can be, for example, 0.2, 0.22, 0.25, 0.26, 0.28 or 0.3, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0016] The composite ferrite for self-biased circulators provided by this invention combines BaM ferrite and LiZn ferrite. LiZn ferrite has the advantages of high remanence ratio, low linewidth and high Curie temperature. With the combination of different types and amounts of substitution elements, the microstructure and electromagnetic properties of the composite ferrite are improved.

[0017] Preferably, the composition of the dopant, based on the total mass percentage of LiZn ferrite and BaM ferrite, includes: Bi2O3 2-2.7wt%, B2O3 0.5-1.5wt%, V2O5 1-1.5wt%, and CuO 1-1.5wt%.

[0018] The mass percentage of Bi2O3 in the dopant accounts for 2-2.7 wt% of the total mass percentage of LiZn ferrite and BaM ferrite. For example, it can be 2 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, or 2.7 wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0019] The mass percentage of B2O3 in the dopant is 0.5-1.5 wt% of the total mass percentage of LiZn ferrite and BaM ferrite, for example, it can be 0.5 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, or 1.5 wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0020] The mass percentage of V2O5 in the dopant is 1-1.5 wt% of the total mass percentage of LiZn ferrite and BaM ferrite, for example, it can be 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt% or 1.5 wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0021] The CuO content in the dopant is 1-1.5 wt% of the total mass content of LiZn ferrite and BaM ferrite, for example, it can be 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt% or 1.5 wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0022] In a second aspect, the present invention provides a method for preparing a composite ferrite for a self-biased circulator as described in the first aspect, the method comprising the following steps:

[0023] (1) LiZn ferrite and BaM ferrite were mixed by first wet milling, and the resulting slurry was dried and pre-calcined in sequence to obtain the precursor.

[0024] (2) The dopant and the precursor obtained in step (1) are mixed by a second wet milling. The resulting slurry is dehydrated and then subjected to magnetic field orientation molding and sintering to obtain the composite ferrite for the self-biased circulator.

[0025] The method for preparing composite ferrite for self-biased circulators provided by this invention effectively controls grain boundary characteristics, improves orientation degree, and increases saturation magnetization through high-energy wet grinding, magnetic field orientation forming, and heat treatment. By combining the types and amounts of substitution elements, the microstructure and electromagnetic properties of composite ferrite are improved, making it suitable for industrial-scale production.

[0026] Preferably, the raw materials for preparing the LiZn ferrite in step (1) include Li2CO3, ZnO, Fe2O3, Co2O3 and Mn3O4.

[0027] Preferably, the raw materials for preparing the BaM ferrite in step (1) include BaCO3, CaCO3, La2O3, Fe2O3 and Co2O3.

[0028] Preferably, the BaM ferrite in step (1) is obtained by sequentially wet ball milling, drying and calcining the raw materials prepared in the specified amount.

[0029] Preferably, the mass ratio of the raw material, deionized water and zirconia balls in the wet ball milling is 1:(0.9-1.1):(5.5-6.5), for example, it can be 1:0.9:5.5, 1:1:6 or 1:1.1:6.5, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0030] Preferably, the wet ball milling is performed at a rotation speed of 70-90 r / min for 8-12 h.

[0031] The rotational speed of the wet ball mill is 70-90 r / min, for example, it can be 70 r / min, 75 r / min, 80 r / min, 85 r / min or 90 r / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0032] The wet ball milling time is 8-12 hours, for example, it can be 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0033] Preferably, a dispersant is added during the wet ball milling process, and the volume ratio of the dispersant to deionized water is 1:(35-45), for example, it can be 1:35, 1:38, 1:40, 1:42 or 1:45, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0034] Preferably, the dispersant comprises any one or a combination of at least two of ammonia, sodium hexametaphosphate, or sodium tripolyphosphate. Typical but non-limiting combinations include a combination of ammonia and sodium hexametaphosphate, a combination of sodium hexametaphosphate and sodium tripolyphosphate, or a combination of ammonia, sodium hexametaphosphate, and sodium tripolyphosphate.

[0035] Preferably, the drying temperature is 115-125℃, for example, it can be 115℃, 118℃, 120℃, 122℃ or 125℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0036] Preferably, the process after drying and before roasting includes a step of passing the material through an 80-mesh sieve.

[0037] Preferably, the roasting temperature is 1180-1250℃ and the time is 1-5h.

[0038] The roasting temperature is 1180-1250℃, for example, it can be 1180℃, 1200℃, 1220℃, 1230℃ or 1250℃, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0039] The roasting time is 1-5 hours, for example, it can be 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0040] Preferably, in step (1), the mass ratio of powder, deionized water and zirconia balls in the first wet milling mixture is 1:(0.9-1.1):(5.5-6.5), for example, it can be 1:0.9:5.5, 1:1:6 or 1:1.1:6.5, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0041] Preferably, in step (1), the rotation speed of the first wet grinding mixture is 60-80 r / min, and the time is 6-10 h.

[0042] Step (1) The rotation speed of the first wet grinding is 60-80 r / min, for example, it can be 60 r / min, 65 r / min, 70 r / min, 75 r / min or 80 r / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0043] Step (1) The first wet grinding mixing time is 6-10h, for example, it can be 6h, 7h, 8h, 9h or 10h, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0044] Preferably, in step (1), a dispersant is added to the first wet milling mixture, and the volume ratio of the dispersant to deionized water is 1:(35-45), for example, it can be 1:35, 1:38, 1:40, 1:42 or 1:45, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0045] Preferably, the dispersant comprises any one or a combination of at least two of ammonia, sodium hexametaphosphate, or sodium tripolyphosphate. Typical but non-limiting combinations include a combination of ammonia and sodium hexametaphosphate, a combination of sodium hexametaphosphate and sodium tripolyphosphate, or a combination of ammonia, sodium hexametaphosphate, and sodium tripolyphosphate.

[0046] Preferably, the drying temperature in step (1) is 115-125°C, for example, it can be 115°C, 118°C, 120°C, 122°C or 125°C, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0047] Preferably, step (1) includes a step of passing the material through an 80-mesh sieve after drying and before pre-firing.

[0048] Preferably, the pre-firing temperature in step (1) is 980-1020℃ and the time is 2-6h.

[0049] The preheating temperature in step (1) is 980-1020℃, for example, it can be 980℃, 990℃, 1000℃, 1010℃ or 1020℃, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0050] The preheating time in step (1) is 2-6 hours, for example, it can be 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0051] Preferably, in step (2), the mass ratio of powder, deionized water and zirconia balls in the second wet milling mixture is 1:(0.9-1.1):(5.5-6.5), for example, it can be 1:0.9:5.5, 1:1:6 or 1:1.1:6.5, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0052] Preferably, in step (2), the rotation speed of the second wet grinding mixture is 70-90 r / min, and the time is 12-18 h.

[0053] In step (2), the rotation speed of the second wet grinding is 70-90 r / min, for example, it can be 70 r / min, 75 r / min, 80 r / min, 85 r / min or 90 r / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0054] Step (2) The second wet milling mixing time is 12-18h, for example, it can be 12h, 14h, 16h or 18h, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0055] Preferably, the water content of the slurry after dehydration in step (2) is 20-30%, for example, it can be 20%, 22%, 25%, 28% or 30%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0056] Preferably, the magnetic field for magnetic field orientation shaping in step (2) is ≥1.4T, for example, it can be 1.4T, 1.5T, 1.6T, 1.7T or 1.8T, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0057] Preferably, the magnetic field orientation forming pressure in step (2) is 2.5-3.5 MPa, for example, it can be 2.5 MPa, 2.8 MPa, 3 MPa, 3.2 MPa or 3.5 MPa, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0058] Preferably, the sintering temperature in step (2) is 1150-1200℃ and the time is 2-6h.

[0059] The sintering temperature in step (2) is 1150-1200℃, for example, it can be 1150℃, 1160℃, 1170℃, 1180℃ or 1200℃, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0060] The sintering time in step (2) is 2-6 hours, for example, it can be 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] The composite ferrite for self-biased circulators provided by this invention combines BaM ferrite and LiZn ferrite. LiZn ferrite has the advantages of high remanence ratio, low linewidth and high Curie temperature. Through high-energy wet grinding, magnetic field orientation forming and heat treatment, the grain boundary characteristics are effectively controlled, the orientation degree is improved and the saturation magnetization is increased. By combining the types and amounts of substitution elements, the microstructure and electromagnetic properties of the composite ferrite are improved, making it suitable for industrial-scale production. Detailed Implementation

[0063] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0064] Example 1

[0065] This embodiment provides a composite ferrite for a self-biased circulator. The raw materials for preparing the composite ferrite for the self-biased circulator include LiZn ferrite, BaM ferrite, and dopant. The mass ratio of LiZn ferrite to BaM ferrite is 1:1.

[0066] The LiZn ferrite is: Li 0.365 Zn 0.27 Fe 2.225 Co 0.04 Mn 0.1 O4, BaM ferrite is: Ba 0.46 Ca 0.18 La 0.36 Fe 11.78 Co 0.22 O 19The composition of the dopant, based on the total mass percentage of LiZn ferrite and BaM ferrite, includes: Bi2O3 2.2wt%, B2O3 0.5wt%, V2O5 1.2wt%, and CuO 1wt%.

[0067] The method for preparing the composite ferrite for the self-biased circulator includes the following steps:

[0068] (1) The raw materials were prepared by wet ball milling at 80 r / min for 10 h. The mass ratio of the raw materials, deionized water and zirconia balls in the wet ball milling was 1:1:6. Sodium hexametaphosphate was added in the wet ball milling, and the volume ratio of sodium hexametaphosphate to deionized water was 1:40. Then, the raw materials were dried at 120℃, passed through an 80-mesh sieve and calcined at 1200℃ for 3 h to obtain BaM ferrite. The raw materials included BaCO3, CaCO3, La2O3, Fe2O3 and Co2O3.

[0069] BaM ferrite and LiZn ferrite were wet-milled together at 70 r / min for 8 h. The mass ratio of powder, deionized water and zirconia balls in the first wet milling was 1:1:6. Sodium hexametaphosphate was added to the first wet milling, and the volume ratio of sodium hexametaphosphate to deionized water was 1:40. The resulting slurry was dried at 120℃, passed through an 80-mesh sieve and pre-calcined at 1000℃ for 4 h to obtain the precursor. The raw materials for the preparation of LiZn ferrite include Li2CO3, ZnO, Fe2O3, Co2O3 and Mn3O4.

[0070] (2) The dopant in the formulation and the precursor obtained in step (1) are mixed in a second wet mill at a speed of 80 r / min for 16 h. The mass ratio of powder, deionized water and zirconium oxide balls in the second wet mill is 1:1:6. After the slurry is dehydrated to a water content of 25%, it is magnetically oriented and shaped under a magnetic field of 1.6T and a pressure of 3MPa. After sintering at 1180℃ for 4 h, the composite ferrite for the self-biased circulator is obtained.

[0071] Example 2

[0072] This embodiment provides a composite ferrite for a self-biased circulator. The raw materials for preparing the composite ferrite for the self-biased circulator include LiZn ferrite, BaM ferrite, and dopant; the mass ratio of LiZn ferrite to BaM ferrite is 1:1.5.

[0073] The LiZn ferrite is: Li 0.335 Zn 0.33 Fe 2.205 Co 0.03 Mn 0.1 O4, BaM ferrite is: Ba 0.4 Ca0.22 La 0.38 Fe 11.8 Co 0.2 O 19 The composition of the dopant, based on the total mass percentage of LiZn ferrite and BaM ferrite, includes: Bi2O3 2wt%, B2O3 1.1wt%, V2O5 1wt%, and CuO 1.3wt%.

[0074] The method for preparing the composite ferrite for the self-biased circulator includes the following steps:

[0075] (1) The raw materials were prepared by wet ball milling at 70 r / min for 12 h. The mass ratio of the raw materials, deionized water and zirconia balls in the wet ball milling was 1:0.9:5.5. Ammonia water was added in the wet ball milling, and the volume ratio of ammonia water to deionized water was 1:35. Then, the raw materials were dried at 115℃, passed through an 80-mesh sieve and calcined at 1180℃ for 5 h to obtain BaM ferrite. The raw materials included BaCO3, CaCO3, La2O3, Fe2O3 and Co2O3.

[0076] BaM ferrite and LiZn ferrite were wet-milled for 10 hours at 60 r / min. The mass ratio of powder, deionized water and zirconia balls in the first wet milling was 1:0.9:5.5. Ammonia water was added in the first wet milling, and the volume ratio of ammonia water to deionized water was 1:35. The resulting slurry was dried at 115℃, passed through an 80-mesh sieve, and pre-calcined at 980℃ for 6 hours to obtain the precursor. The raw materials for preparing the LiZn ferrite included Li2CO3, ZnO, Fe2O3, Co2O3 and Mn3O4.

[0077] (2) The dopant in the formulation and the precursor obtained in step (1) are mixed in a second wet mill at a speed of 70 r / min for 18 h. The mass ratio of powder, deionized water and zirconium oxide balls in the second wet mill is 1:0.9:5.5. After the slurry is dehydrated to a water content of 20%, it is magnetically oriented and shaped under a magnetic field of 1.5T and a pressure of 2.5MPa. After sintering at 1150℃ for 6 h, the composite ferrite for the self-biased circulator is obtained.

[0078] Example 3

[0079] This embodiment provides a composite ferrite for a self-biased circulator. The raw materials for preparing the composite ferrite for the self-biased circulator include LiZn ferrite, BaM ferrite, and dopant; the mass ratio of LiZn ferrite to BaM ferrite is 1:2.

[0080] The LiZn ferrite is: Li 0.35 Zn 0.3 Fe2.23 Co 0.02 Mn 0.1 O4, BaM ferrite is: Ba 0.32 Ca 0.26 La 0.42 Fe 11.72 Co 0.28 O 19 The composition of the dopant, based on the total mass percentage of LiZn ferrite and BaM ferrite, includes: Bi2O3 2.7wt%, B2O3 1.1wt%, V2O5 1.2wt%, and CuO 1.5wt%.

[0081] The method for preparing the composite ferrite for the self-biased circulator includes the following steps:

[0082] (1) The raw materials were prepared by wet ball milling at 90 r / min for 8 h. The mass ratio of the raw materials, deionized water and zirconia balls in the wet ball milling was 1:1.1:6.5. Sodium tripolyphosphate was added in the wet ball milling, and the volume ratio of sodium tripolyphosphate to deionized water was 1:45. Then, the raw materials were dried at 125℃, passed through an 80-mesh sieve and calcined at 1250℃ for 1 h to obtain BaM ferrite. The raw materials included BaCO3, CaCO3, La2O3, Fe2O3 and Co2O3.

[0083] BaM ferrite and LiZn ferrite were wet-milled together at 80 r / min for 6 h. The mass ratio of powder, deionized water and zirconia balls in the first wet milling was 1:1.1:6.5. Sodium tripolyphosphate was added to the first wet milling, and the volume ratio of sodium tripolyphosphate to deionized water was 1:45. The resulting slurry was dried at 125℃, passed through an 80-mesh sieve, and pre-calcined at 1020℃ for 2 h to obtain the precursor. The raw materials for preparing the LiZn ferrite included Li2CO3, ZnO, Fe2O3, Co2O3 and Mn3O4.

[0084] (2) The dopant in the formulation and the precursor obtained in step (1) are mixed in a second wet mill at a speed of 90 r / min for 12 h. The mass ratio of powder, deionized water and zirconium oxide balls in the second wet mill is 1:1.1:6.5. After the slurry is dehydrated to a water content of 30%, it is magnetically oriented and shaped under a magnetic field of 1.4T and a pressure of 3.5MPa. After sintering at 1200℃ for 2 h, the composite ferrite for the self-biased circulator is obtained.

[0085] Example 4

[0086] This embodiment provides a composite ferrite for a self-biased circulator, differing from Embodiment 1 in that the LiZn ferrite is adjusted to Li 0.355 Zn 0.29 Fe2.205 Co 0.05 Mn 0.1 O4, BaM ferrite is adjusted to Ba 0.38 Ca 0.28 La 0.34 Fe 11.7 5Co 0.25 O 19 The mass ratio of LiZn ferrite to BaM ferrite is adjusted to 1:2.5, and the sodium hexametaphosphate in step (1) is adjusted to a mixture of sodium hexametaphosphate and sodium tripolyphosphate at a mass ratio of 1:1. The rest is the same as in Example 1.

[0087] Example 5

[0088] This embodiment provides a composite ferrite for a self-biased circulator, differing from Embodiment 1 in that the LiZn ferrite is adjusted to Li 0.345 Zn 0.31 Fe 2.215 Co 0.03 Mn 0.1 O4, BaM ferrite is adjusted to Ba 0.36 Ca 0.2 La 0.44 Fe 11.7 Co 0.3 O 19 The mass ratio of LiZn ferrite to BaM ferrite is adjusted to 1:1.8, and the sodium hexametaphosphate in step (1) is adjusted to a mixture of ammonia and sodium tripolyphosphate at a mass ratio of 1:1. The rest is the same as in Example 1.

[0089] Example 6

[0090] This embodiment provides a composite ferrite for a self-biased circulator. The preparation method of the composite ferrite for the self-biased circulator differs from that of Embodiment 1 in that, except that the pre-calcination temperature in step (1) is adjusted to 950°C and the sodium hexametaphosphate in step (1) is adjusted to a mixture of sodium hexametaphosphate, ammonia, and sodium tripolyphosphate in a mass ratio of 1:1:1, the rest are the same as in Embodiment 1.

[0091] Example 7

[0092] This embodiment provides a composite ferrite for a self-biased circulator. The preparation method of the composite ferrite for the self-biased circulator differs from that of Embodiment 1 in that, except that the pre-calcination temperature in step (1) is adjusted to 1050°C and the sodium hexametaphosphate in step (1) is adjusted to a mixture of sodium hexametaphosphate, ammonia, and sodium tripolyphosphate in a mass ratio of 1:1:1, the rest are the same as in Embodiment 1.

[0093] Example 8

[0094] This embodiment provides a composite ferrite for a self-biased circulator. The preparation method of the composite ferrite for the self-biased circulator differs from that of Embodiment 1 in that sodium hexametaphosphate is not added in the first wet milling and mixing step (1), while the rest is the same as in Embodiment 1.

[0095] Example 9

[0096] This embodiment provides a composite ferrite for a self-biased circulator. The difference between the preparation method of the composite ferrite for the self-biased circulator and that of Embodiment 1 is that the magnetic field for magnetic field orientation forming in step (2) is adjusted to 1.2T, while the rest is the same as that of Embodiment 1.

[0097] Comparative Example 1

[0098] This comparative example provides a composite ferrite for a self-biased circulator, which differs from Example 1 in that the LiZn ferrite is adjusted to Li 0.35 Zn 0.3 Fe 2.21 Co 0.04 Mn 0.1 O4, BaM ferrite is adjusted to Ba 0.42 Ca 0.2 La 0.38 Fe 11.76 Co 0.24 O 19 The mass ratio of LiZn ferrite to BaM ferrite was adjusted to 1:4, and all other aspects were the same as in Example 1.

[0099] Comparative Example 2

[0100] This comparative example provides a composite ferrite for a self-biased circulator, which differs from Example 1 in that the LiZn ferrite is adjusted to Li 0.365 Zn 0.27 Fe 2.215 Co 0.05 Mn 0.1 O4, BaM ferrite is adjusted to Ba 0.34 Ca 0.24 La 0.42 Fe 11.7 4Co 0.26 O 19 The mass ratio of LiZn ferrite to BaM ferrite was adjusted to 1:0.5, and all other aspects were the same as in Example 1.

[0101] The self-biased circulators provided in Examples 1-9 and Comparative Examples 1 and 2 were prepared using composite ferrite, and the saturation magnetization was tested at 4πM. s Remanence ratio M r / M s Ferromagnetic resonance linewidth ΔH, dielectric constant εr Coercivity H c The results are shown in Table 1.

[0102] Table 1

[0103] Example 1 4113 0.92 304 15.3 2622 Example 2 4056 0.9 317 15.3 2628 Example 3 4198 0.9 324 15.4 2636 Example 4 4076 0.91 308 15.2 2639 Example 5 4181 0.92 329 15.6 2644 Example 6 4076 0.87 562 15.3 2038 Example 7 4091 0.86 537 15.2 1845 Example 8 4123 0.82 769 15.2 1846 Example 9 4056 0.84 467 15.3 1756 Comparative Example 1 4073 0.9 342 15.6 2851 Comparative Example 2 4053 0.9 286 15 2336

[0104] As can be seen from Table 1, the composite ferrite for self-biased circulators provided by the present invention has advantages such as high saturation magnetization, high remanence ratio, low linewidth, high dielectric constant, and high coercivity.

[0105] A comparison of Example 1 with Examples 6 and 7 shows that if the pre-firing temperature is too low or too high, the linewidth will increase and the coercivity will decrease. A comparison of Example 1 with Example 8 shows that if no dispersant is added during wet ball milling, the composition will shift, the linewidth will increase, and the remanence and coercivity will decrease. A comparison of Example 1 with Example 9 shows that if the magnetic field of the magnetic field orientation molding is too low, the remanence and coercivity will decrease.

[0106] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that if the content of each component in LiZn ferrite and BaM ferrite exceeds the limit, it will lead to a decrease in the overall electromagnetic performance, thereby affecting its application in self-biased circulators.

[0107] In summary, the composite ferrite for self-biased circulators provided by this invention combines BaM ferrite with LiZn ferrite. LiZn ferrite has the advantages of high remanence ratio, low linewidth and high Curie temperature. Through high-energy wet grinding, magnetic field orientation forming and heat treatment, the grain boundary characteristics are effectively controlled, the orientation degree is improved and the saturation magnetization is increased. With the combination of the type and amount of substitution elements, the microstructure and electromagnetic properties of the composite ferrite are improved, making it suitable for industrial-scale production.

[0108] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A composite ferrite for a self-biased circulator, characterized in that, The raw materials for preparing the composite ferrite for the self-biased circulator include LiZn ferrite, BaM ferrite, and dopant; the mass ratio of LiZn ferrite to BaM ferrite is 1:(1-2.5). The LiZn ferrite is: Li 0.5-0.5a Zn a Fe 2.4-0.5a-b Co b Mn 0.1 O4, where 0.27≤a≤0.33, 0.02≤b≤0.06; The BaM ferrite is: Ba 1-x-y Ca x La y Fe 12-z Co z O 19 Where 0.18≤x≤0.28, 0.34≤y≤0.44, and 0.2≤z≤0.3; The self-biased circulator composite ferrite is prepared by the following method, which includes the following steps: (1) LiZn ferrite and BaM ferrite are mixed by first wet milling, and the resulting slurry is dried and pre-calcined in sequence to obtain a precursor; a dispersant is added in the first wet milling; the pre-calcination temperature is 980-1020℃; (2) The dopant and the precursor obtained in step (1) are mixed by a second wet milling. The resulting slurry is dehydrated and then subjected to magnetic field orientation molding and sintering to obtain the composite ferrite for the self-biased circulator. The magnetic field of the magnetic field orientation molding is ≥1.4T.

2. The composite ferrite for a self-biased circulator according to claim 1, characterized in that, Based on the total mass percentage of LiZn ferrite and BaM ferrite, the composition of the dopant includes: Bi2O3 2-2.7wt%, B2O3 0.5-1.5wt%, V2O5 1-1.5wt%, and CuO 1-1.5wt%.

3. A method for preparing a composite ferrite for a self-biased circulator as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: (1) LiZn ferrite and BaM ferrite are mixed by first wet milling, and the resulting slurry is dried and pre-calcined in sequence to obtain a precursor; a dispersant is added in the first wet milling; the pre-calcination temperature is 980-1020℃; (2) The dopant and the precursor obtained in step (1) are mixed by a second wet milling. The resulting slurry is dehydrated and then subjected to magnetic field orientation molding and sintering to obtain the composite ferrite for the self-biased circulator. The magnetic field for the magnetic field orientation shaping is ≥1.4T.

4. The preparation method according to claim 3, characterized in that, The raw materials for preparing the LiZn ferrite in step (1) include Li2CO3, ZnO, Fe2O3, Co2O3 and Mn3O4.

5. The preparation method according to claim 3, characterized in that, The raw materials for preparing BaM ferrite in step (1) include BaCO3, CaCO3, La2O3, Fe2O3 and Co2O3.

6. The preparation method according to claim 3, characterized in that, The BaM ferrite in step (1) is obtained by sequentially wet ball milling, drying and calcining the raw materials prepared in the specified amount.

7. The preparation method according to claim 6, characterized in that, The mass ratio of raw materials, deionized water, and zirconia balls in the wet ball milling process is 1:(0.9-1.1):(5.5-6.5).

8. The preparation method according to claim 6, characterized in that, The wet ball milling speed is 70-90 r / min, and the time is 8-12 h.

9. The preparation method according to claim 6, characterized in that, A dispersant is added during the wet ball milling process, and the volume ratio of the dispersant to deionized water is 1:(35-45).

10. The preparation method according to claim 6, characterized in that, The drying temperature is 115-125℃.

11. The preparation method according to claim 6, characterized in that, The roasting temperature is 1180-1250℃, and the time is 1-5h.

12. The preparation method according to claim 3, characterized in that, In step (1), the mass ratio of powder, deionized water and zirconia balls in the first wet milling mixture is 1:(0.9-1.1):(5.5-6.5).

13. The preparation method according to claim 3, characterized in that, Step (1) The rotation speed of the first wet grinding mixture is 60-80 r / min, and the time is 6-10 h.

14. The preparation method according to claim 3, characterized in that, The volume ratio of the dispersant to deionized water in step (1) is 1:(35-45).

15. The preparation method according to claim 3, characterized in that, The drying temperature in step (1) is 115-125℃.

16. The preparation method according to claim 3, characterized in that, The preheating time in step (1) is 2-6 hours.

17. The preparation method according to claim 3, characterized in that, In step (2), the mass ratio of powder, deionized water and zirconia balls in the second wet milling mixture is 1:(0.9-1.1):(5.5-6.5).

18. The preparation method according to claim 3, characterized in that, In step (2), the rotation speed of the second wet grinding mixture is 70-90 r / min, and the time is 12-18 h.

19. The preparation method according to claim 3, characterized in that, In step (2), the dewatering process is carried out until the moisture content of the slurry is 20-30%.

20. The preparation method according to claim 3, characterized in that, The pressure for magnetic field orientation forming in step (2) is 2.5-3.5 MPa.

21. The preparation method according to claim 3, characterized in that, The sintering temperature in step (2) is 1150-1200℃ and the time is 2-6h.

Citation Information

Patent Citations

  • Soft and hard magnetic microwave ferrite coupling material and preparation method thereof

    CN118955113A

  • C-band ultralow-loss self-biased hexagonal gyromagnetic ferrite material and preparation method thereof

    CN119176714A

  • High-coercivity ferrite and preparation method thereof

    CN113087513A

  • Low-loss LiZnTiMn gyromagnetic ferrite material and preparation method thereof

    CN113845359A